Peningkatan Produksi Dan Pengembangan Ikan Asap Kelompok Usaha Pokhlashar Medudulu Di Desa Basule Kecamatan Lasolo Kabupaten Konawe Utara - Ridha Taurisma Lajaria; Lucia Evianti Patulak; Wa Ode Dien Indalestari; Dr.H.M. Zabir Zainuddin; Imran; Nur Aisyah; Muh. Fahri (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Marketing strategy is very important for smoked fish producers to achieve their goals, so to run a business it is necessary to develop a marketing strategy. The method used to achieve the goal is socialization using participatory learning techniques and mentoring as well as direct practice in the field. This method places participants as both objects and subjects in the training process. The results of the evaluation of this activity were that participants gave a positive response, based on participants' comments which stated that the material provided was very beneficial, especially marketing activities, namely focusing on products, pricing, policies and promotional methods or what is known as Marketing Strategy. . In this way, you can build enthusiasm to advance your business and family.